Analysis of Health Workforce Retention and Attraction Policies in Lao PDR - Vangkonevilay, Phouthone; Paphassarang, Chanthakhath; Theppanya, Khampasong; Phathammavong, Outavong; Rotem, Arie (World Bank, Washington, DC, 2015)
Worldwide, Lao PDR has been identified among 57 countries with a critical shortage and skewed distribution of its health workforce, especially in remote and rural areas (Guilbert 2006, World Bank 2015). Healthcare education is provided by the public sector through nine public health training institutes in the country: The University of Health Sciences (UHS) in Vientiane Capital provides medical related programs including medicine, dentistry, pharmacy, medical technology, nursing basic sciences and post graduate studies, with the other institutions located at provincial levels: three Regional Public Health Colleges, four Provincial Public Health Schools and one Nursing School. The annual output from these institutions is approximately 2,000 (Department of Organization and Personnel (DOP), 2013). This study focuses on supply-side policies to determine the key challenges and policy implications regarding improved availability and retention of staff in remote areas. This possibly stems from, among other reasons, the following: (a) limited government quotas to recruit and place health workers in rural areas (i.e. in 2013 1,045 recruitment quotas were allocated to MOH, of which 882 (84.4 percent) were given to provinces, districts and health centers nationwide); (b) health workers’preference to work in urban areas with better income and professional career development opportunities; and (c) low self-confidence of new graduates to work independently in rural areas which is attributable to insufficient clinical practice during training, due in part to the excessive number of student intakes to training institutes. The shortage of middle and high level health workers at primary and secondary health care facility levels leads to a major gap in access to quality health care services between urban and rural areas.